Optimal fluorite/gypsum mineralizer ratio in Portland cement clinkering - J. I. Tobón (Materiales de Construccion, 2016)
This paper presents an analysis of the joint effect of fluorite and gypsum as mineralizers in the manufacture of Portland cement. A laboratory- scale Box-Behnken statistical design was used to quantify the effects of the explanatory variables fluorite content (0.00, 0.25, 0.50, and 0.75%), fluorite/gypsum ratio (2/15, 1/3 and 8/15), and clinkering temperature (1250, 1300, and 1350 °C) on the response variable free CaO content in the clinker produced. The clinker was characterized by the ethylene method, XRD, DSC and optical microscopy. Free CaO decreases of 81% and 56% were found in the mineralized clinker, compared to the same clinker without mineralizers, at 1300 °C and 1250 °C, respectively. Petrographic analysis showed that at lower temperatures, the amount of alite in the mineralized clinker was higher than the amount of alite in the clinker without mineralizers. The best condition was found for the fluorite/gypsum ratio of 2/15.